Valproic Acid 투여로 인한 약인성 떨림 환자의 한방 치료 치험 1례 - 장한솔; 하유빈; 정승현; Jang, Hansol; Ha, Yu-bin; Jung, Seung-hyun (대한한방내과학회지, 2021)
A 56-year-old male patient with a sudden onset of tremor and involuntary movement of right upper and lower extremities, head, and voice was diagnosed as having a drug-induced tremor, with valproic acid being the culprit drug. The patient had undergone admission treatment at an internal Korean medicine department with herbal medicine according to constitutional diagnosis, acupuncture, moxibustion, cupping, and rehabilitation. The change in the severity of tremor was assessed with the Fahn Tolosa Marine scale. After discharge, the patient took herbal medicine for two more months. After 20 days of admission and 2 months of treatment with herbal medicine, the patient's tremor improved. In this case, the patient with valproic acid-induced tremor showed improvement in symptoms after 20 days of hospitalization and further reduction of tremor and improvement of quality of life were confirmed through follow-up for 2 months.